Serial Case: Colorectal Malignancy in Young Age - Lia Sasmithae; Bogi Pratomo (The Indonesian Society for Digestive Endoscopy, 2017)
Colorectal cancer was the third most common cancer found worldwide. In 2002, colorectal cancer was the 2nd most common cancer in men, while it ranked third among women. Based on Indonesian Ministry of Health data, its prevalence was 1.8 per 100.000 population. We report four cases of colorectal cancer in this case series, and all cases was occured among person aged 28-32 years old. Age was the main relevant risk factors for colorectal cancer in most population. Only 3% of colorectal cancer found in individual aged less than 40 years old. This case series also aimed to show that risk factors was various and changing by the time, but its determinant factors could not be explained yet.